Effects of hydrogen and oxygen enrichment on performance and emissions of an SI engine under idle operating condition - Karagoz, Yasin; Sandalci, Tarkan; Dalkilic, Ahmet Selim (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Hydrogen as supplementary fuel can enhance combustion characteristics and emission in spark ignition engines at idle operating condition. In this study, hydrogen and oxygen were simultaneously produced by means of a conventional electrolyser and consumed to eliminate the requirement of a storage device. Tests were conducted on a 1.1 litter Peugeot SI engine as a representative of small engine powered vehicles. The engine was modified to operate with the mixture of gasoline and hydrogen + oxygen. A self-developed ECU was used to control hydrogen injectors. All the tests were carried out under idle condition and hydrogen + oxygen gas mixture were used as supplementary fuel. Various hydrogen energy fractions such as 0%, 5%, 8%, 10% and 15% were selected and the effect of hydrogen addition on coefficient of variation in the engine speed, coefficient of variation in the indicated mean effective pressure, peak in-cylinder temperature, energy flow rate, indicated thermal efficiency, indicated specific fuel consumption, THC, CO, and NOx emissions were investigated under idle condition. According to experimental results, coefficient of variation in the engine speed, coefficient of variation in the indicated mean effective pressure, energy flow rate, indicated thermal efficiency, indicated specific fuel consumption, peak in-cylinder temperature, THC and CO were improved with the increase of hydrogen energy fraction. However, the dramatic increase of NOx emissions couldn't be prevented with increasing amount of hydrogen and oxygen. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen enrichment; Idle running; Oxides of nitrogen; Carbon monoxide; Coefficient of variation; SPARK-IGNITION ENGINE; GASOLINE-ENGINE; NATURAL-GAS; EXHAUST EMISSIONS; DIESEL-ENGINE; DUAL FUEL; COMBUSTION CHARACTERISTICS; PASSENGER CAR; INJECTION; ETHANOL; Chemistry; Electrochemistry; Energy & Fuels